Grainyhead‐like 3 (Grhl3) deficiency in brain leads to altered locomotor activity and decreased anxiety‐like behaviors in aged mice. Issue 6 (3rd February 2017) - Dworkin, Sebastian; Auden, Alana; Partridge, Darren D.; Daglas, Maria; Medcalf, Robert L.; Mantamadiotis, Theo; Georgy, Smitha R.; Darido, Charbel; Jane, Stephen M.; Ting, Stephen B.
ABSTRACT: The highly conserved Grainyhead‐like ( Grhl ) family of transcription factors, comprising three members in vertebrates ( Grhl1‐3 ), play critical regulatory roles during embryonic development, cellular proliferation, and apoptosis. Although loss of Grhl function leads to multiple neural abnormalities in numerous animal models, a comprehensive analysis of Grhl expression and function in the mammalian brain has not been reported. Here they show that only Grhl3 expression is detectable in the embryonic mouse brain; particularly within the habenula, an organ known to modulate repressive behaviors. Using both Grhl3 ‐knockout mice ( Grhl3 −/− ), and brain‐specific conditional deletion of Grhl3 in adult mice ( Nestin‐Cre/Grhl3 flox/flox ), they performed histological expression analyses and behavioral tests to assess long‐term effects of Grhl3 loss on motor co‐ordination, spatial memory, anxiety, and stress. They found that complete deletion of Grhl3 did not lead to noticeable structural or cell‐intrinsic defects in the embryonic brain; however, aged Grhl3 conditional knockout ( cKO ) mice showed enlarged lateral ventricles and displayed marked changes in motor function and behaviors suggestive of decreased fear and anxiety. They conclude that loss of Grhl3 in the brain leads to significant alterations in locomotor activity and decreased self‐inhibition, and as such, these mice may serve as a novel model of human conditions of impulsive behavior or hyperactivity. © 2017 Wiley Periodicals, Inc. Develop Neurobiol 77: 775–788, 2017